The Charles Davidson Bell Heritage Trust collection : a catalogue and critical study, - Lipschitz, Michael Roy (Department of Historical Studies, 2017)
This thesis comprises two parts. Part One is a biography of the life of Charles Davidson Bell (1813-1882), who was the Surveyor General at the Cape from 1848 to 1872. Part Two consists of an illustrated catalogue and critical study of the the pictures by Charles Davidson Bell in the Bell Heritage Trust Collection at U.C.T. The Biography of Charles Davidson Bell has been researched from unpublished sources and from secondary published sources. The chronology of his life is placed in relationship with his versatile accomplishments as an artist and his achievements in other diverse fields. In the Catalogue, the history, formation and restoration of the Bell Heritage Trust collection is reviewed. The criteria used in cataloguing and attribution of pictures is discussed. The cataloguing terminology that has been employed, is defined. The various collections of sketchbooks are introduced and discussed in terms of the ordering and arrangement of the pictures. The pictures are catalogued and placed in their historical context. The inter-relationship between pictures in the Bell Heritage Trust and in other collections is considered.